Reflection-phase spectra of cavity-resonator-integrated guided-mode resonance devices. (8th June 2017) - Inoue, Junichi; Okuda, Hiroki; Kintaka, Kenji; Nishio, Kenzo; Ura, Shogo
Abstract: A cavity-resonator-integrated guided-mode resonance filter (CRIGF) consisting of waveguide gratings on a transparent substrate can provide not only a narrowband reflection spectrum but also a steep reflection-phase spectrum. Reflection-phase spectra of CRIGFs were discussed in detail theoretically with an analytical expression. It was found that CRIGFs can be categorized into two types showing a phase variation of 2π rad, namely, reflection-phase rotation, or no rotation. On the other hand, the same structure on a high-reflection mirror, instead of the transparent substrate, normally shows the rotation. The two types of CRIGFs were designed and fabricated with different core thicknesses so that theoretically predicted reflection-phase characteristics with and without rotation could be demonstrated experimentally.